Evaluation method of fatigue life for weld joints with defects in the horizontal restraint components of main steam pipelines. (November 2021) - Shen, Mengling; Chang, Haijun; Yang, Yuansong; Qi, Shuo; Hou, Junxia
Abstract: Horizontal restraint components are mainly used in nuclear power plants to limit the horizontal displacement of the "super pipelines", such as the main steam pipelines and main water supply pipelines. Horizontal restraint components are very important for ensuring the safety of the second loop of nuclear power plants under unexpected conditions. However, because the size of the horizontal restraint components are quite large, and the pipelines are complicated, defects or cracks easily occur in the weld joints connected with the components and pipelines. The fatigue crack growth in the weld joints is one of the important reasons of the fatigue failure for the horizontal restraint components. Therefore, investigating the fatigue crack growth of the weld joints is significant to accurately predict the service life of the horizontal restraint components. In this paper, multiple cracks were found in the weld joints of horizontal restraint components in a nuclear power plant. In order to evaluate the fatigue life of the weld joints, fatigue crack growth tests were carried out under different temperature. The material parameters, C and n, of the Paris Equation for the weld joints were obtained and compared with those for the base metal (ferrite steel) in the ASME code. Results showed that the results show that the fatigue crack growth rate of the weld joints in the room temperature is lower first and then higher than that of the material in the high temperature weld joints and the base metal at room temperature, but the fatigue crack growth rate of the weld joints in the high temperature is always higher than that of the base metal at room temperature. The fatigue life of the horizontal restraint components calculated by the Paris Equation from the experiments is quite different compared with the fatigue life calculated from the base metal (ferrite steel) in the ASME code at room temperature.